(untitled) (International journal of artificial intelligence, 2024)
This article covers the topic of social culture and personal success. At the same time, the influence of social culture on personal success is described. The study comprehensively analyzed the influence of factors such as cultural values, family environment, education system, work environment and mass media on personal success. The main goal of the research is to determine the main factors of personal success and to understand how social culture affects this process.